Gender-Related Beliefs, Norms, and the Link With Green Consumption - Zhao, Ziyue; Gong, Yuanchao; Li, Yang; Zhang, Linxiu; Sun, Yan (Frontiers in Psychology, 2021)
Although extant literature provided abundant evidence that men and women were different in their environmental behaviors, there was a lack of an integration of gender differences in green consumption and the underlying mechanism that associates with these disparities. Therefore, to solve this existing gap, the current paper reviewed existing literature in green consumption with three-fold purposes. First, presenting an integrated view of gender different green consumption pattern along with the relationship of gender-related beliefs and individuals’ pro-environmental behavior based on existing evidence. Second, interpreting how gender differences are generated based on the value-belief-norm theory, and the theory of social roles. Third, analyzing previous studies, providing implications for future research and then proposing suggestions for marketing practitioners in green products industry. Accordingly, this article compared men’s and women’s different behavior in green consumption, discussed how and why they behave differently. Generally, women show a more positive green consumption intention, consume less carbon, and purchase green products more frequently. Whereas, men are doing better than women in terms of environmental knowledge, and in some regions, they express higher concerns about environmental problems. It interprets individual differences in green consumption based on VBN theory from a unique insight—gender. It also identified some barriers for both men and women to participate in green consumption, and then proposed several suggestions to improve the public willingness of engaging in green consumption.